EFEKTIVITAS BLENDED LEARNING BERBASIS PROYEK PADA KURIKULUM MERDEKA BELAJAR - Septi Wulandari; Nada Sawita; Rustam Rustam (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
Abstract The purpose of this research is to see the effectiveness of project-based blended learning. The research method used is qualitative. The approach used is a case study. The data in this study are the results of interviews with teachers. The source of this research data is the teacher. In testing the validity of the researchers using the validity of the data. The results showed that 50% of blended learning was effective when offline because it was able to improve critical thinking skills and profiles of Pancasila students. However, 50% is not effective when used online because of the unavailability of online equipment, after that it is difficult to supervise students which causes students to be dishonest. Further research is needed to strengthen this research by examining using statistical data on the effectiveness of learning using blended learning. Keywords: blended learning, effectiveness, Pancasila student profile, critical thinking, project